“Days of Living Archaeology” at the Prehistoric Archaeopark Vsestary, Czech Republic - Radomír Tichý (EXARC, 2017)
Until recently, the presentation of archaeology in the Czech Republic was solely connected to classic museum exhibitions. Unfortunately, not all museums have archaeological exhibitions. For example, the National Museum in Prague currently does not have any, not even temporary, archaeological exhibition due to the reconstruction of the historical building. With the exception of the successful exhibition Lovci mamutů (Mammoth hunters) archaeology was present only as a side topic in temporary exhibitions. Another example of missing permanent archaeological exhibition is from Eastern Bohemia, the regional museum in Hradec Králové. This situation led to the founding of the Prehistoric Archaeopark Všestary.